Pengenalan Open Journal System (OJS) untuk Publikasi Ilmiah Mahasiswa - Elly Astuti; Isharijadi Isharijadi (Jurnal Pengabdian Pada Masyarakat, 2019)
INTRODUCTION OF OPEN JOURNAL SYSTEM FOR SCIENTIFIC PUBLICATION OF STUDENTS. This activity is intended to provide understanding for students that according to the latest regulations, students are required to conduct scientific publications. Scientific publications are intended to communicate the results of academic research carried out to contribute to the development of science. However, many students do not understand how to publish their work properly. This training provides material on the ethics of scientific publications and how to submit articles in scientific journals. Students are introduced to ways to find accredited journals in accordance with the field of study. This is done to avoid student publications in predatory journals. As a result of this activity, students understand the business processes of journals for the scientific publication of their work. They also learned that each journal had its own unique style of environment so they had to pay close attention to the author’s guidelines.